ANALISIS PEMBELAJARAN DAN LITERASI MATEMATIKA SERTA KARAKTER SISWA MATERI GEOMETRI DAN PENGUKURAN (Universitas Negeri Semarang, 2014)
AbstrakSecara umum tujuan penelitian ini dideskripsikannya proses pembelajaran dankemampuan literasi matematika serta karakter siswa pada materi geometri danpengukuran menggunakan analisis POAC. Penelitian ini merupakan jenis penelitiankualitatif. Bentukpendekatanpenelitian yangdigunakan adalah pendekatandeskriptif.Pengumpulandata dilakukan denganangket, observasi,wawancara,dadokumentasi.Sumberdata utama adalah gurumatematika dan siswa.Keabsahandatayangdigunakan dalampenelitian inidenganmenggunakan uji credibility,ujitransferability,ujidependability,uji dependability,dan uji confirmability.Hasilpenelitianyangdidapatkan bahwaproses pembelajarandankemampuanliterasimatematikasertakarakter siswapada materi geometridan pengukuran kelasVIIISMPN 1 TulismenggunakananalisisPOACtelah dilakukanberdasarkananalisisPOAC.Prosespembelajaranmatematika diidentifikasiberdasarkanprosespengajarandanprosesbelajar.Kemampuanliterasi matematikasiswarendah karenahanyamencapailevel4.AbstractThe general research questions in this study how the learning process and maths literacy skillsas well as the character of the students on the geometry material and the measurement usingPOAC analysis. Generally this study’s aim are described the learning process and mathematicsliteracyskillsas well as the characterof the students on the geometry material and themesurement of eight class of Junior High School 1 Tulis using POAC analysis. This is a kindof qualifative sudy. The form of study approached were used descriptive observation, interviews,and documentation. Themain data source were mathematics teachersand students.Thevalidity data was used by using thetest of credibility. The test used in this study wereTesof transferability, test of dependabrility, and test of confirmability. The result of the studythat the learning process and maths literacy skills as well as the character of the students onthe geometry material and the measurement of the eight class of Junior High School 1 Tulisusing POAC analysis has been done based on the POAC analysis. Mathematics learning processwasidentified based onthe processof teaching and learning. Mathematics literacy skillsof students was low because only reached level 4.